2011
DOI: 10.1007/s10853-011-5711-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and dynamic mechanical properties of blends of bitumen with metallocene catalyzed polyolefins

Abstract: A high penetration grade bitumen has been blended with up to 50 wt% of two different grades of metallocene catalyzed linear low density polyethylene (m-LLDPE) in order to investigate the potential of these and similar copolymers as a substitute for styrene butadiene styrene triblock copolymers in polymer-modified bitumens (PMB). A continuous polymer-rich phase was observed at m-LLDPE contents as low as 5-10 wt%, along with a significant decrease in the effective glass transition temperature of the PMBs with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is suggested that the metallocene catalysis controls the molar mass distribution and molecular structure providing polymers with uniform distribution of short chains and narrow molar mass distribution [ 213 ]. This results in reducing the melt elasticity and tuning of bulk properties such as crystallinity and viscosity, consequently increasing the dispersion [ 214 ]. Spadaro et al [ 214 ] used two different grades of metallocene catalysed LLDPE for blending with bitumen in order to validate the possible potential use of these polymers as bitumen modifiers.…”
Section: Virgin and Waste (Recycled) Plastomers To Improve Bitumen Performancementioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the metallocene catalysis controls the molar mass distribution and molecular structure providing polymers with uniform distribution of short chains and narrow molar mass distribution [ 213 ]. This results in reducing the melt elasticity and tuning of bulk properties such as crystallinity and viscosity, consequently increasing the dispersion [ 214 ]. Spadaro et al [ 214 ] used two different grades of metallocene catalysed LLDPE for blending with bitumen in order to validate the possible potential use of these polymers as bitumen modifiers.…”
Section: Virgin and Waste (Recycled) Plastomers To Improve Bitumen Performancementioning
confidence: 99%
“…This results in reducing the melt elasticity and tuning of bulk properties such as crystallinity and viscosity, consequently increasing the dispersion [ 214 ]. Spadaro et al [ 214 ] used two different grades of metallocene catalysed LLDPE for blending with bitumen in order to validate the possible potential use of these polymers as bitumen modifiers. It was observed that the addition of metallocene-catalysed LLDPE enhanced both thermal and mechanical properties of modified bitumen.…”
Section: Virgin and Waste (Recycled) Plastomers To Improve Bitumen Performancementioning
confidence: 99%
“…For this reason, their main application is in asphaltic roofing membranes, where the high-shear mixing phase is followed by a rapid cooling that freezes the morphology, which remains kinetically stable during room-temperature storage. Nevertheless, extensive literature on olefinic PMAs for paving applications is available (see e.g., [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93]), but storage stability is not often mentioned.…”
Section: Asphalt/polyolefins Compatibilitymentioning
confidence: 99%